Characterization of a Double-Loop Four-Josephson-Junction Flux Qubit with Controllable Energy Gap - Shimazu, Y.; Saito, Y.; Wada, Z. (Current Research Progress in Physical Science Vol. 3, 2024)
Superconducting qubits are employed for the practical implementation of scalable quantum information processors. Fault-tolerant quantum computation schemes using superconducting qubits is under intensive study. Among the various kinds of superconducting qubits, flux qubits have a significant advantage in that they can be made insensitive to randomly fluctuating charges in the substrate. Here, the characterization results of a double-loop four-Josephson-junction flux qubit is reported. By varying the magnetic flux in one of the two loops, the energy gap at the classical degeneracy point can be controlled in situ. The basic operation of the system is illustrated by the appearance of a qubit step on a two-dimensional flux map. The energy gap can be indirectly estimated from the shape of the qubit step. The dependence of the shape of the qubit step on the control flux, which is analyzed in terms of the step height and maximum slope, is in good agreement with the simulation results, thereby implicitly indicating that the energy gap is varied from almost zero, less than the thermal energy, to a value higher than 50 GHz. Spectroscopic measurements directly demonstrated the controllability of the energy gap. In addition, doublet splitting due to intercell tunneling was observed for the first time.